2002
DOI: 10.1002/mus.10201
|View full text |Cite
|
Sign up to set email alerts
|

Repetitive nerve stimulation of the nasalis muscle: Technique and normal values

Abstract: A technique of repetitive nerve stimulation of the facial nerve with recording from the nasalis and orbicularis oculi muscles was developed and tested in 15 healthy subjects. Quality criteria were that the stimulus artifact should return to baseline before the onset of the compound muscle action potential (CMAP), and that the CMAP should begin with a negative phase, be biphasic in shape, and have an amplitude of over 1 mV. Repetitive nerve stimulation was only performed if all four criteria were met, which was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
14
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 15 publications
1
14
0
Order By: Relevance
“…The choice of frontalis was based on the historical routine use of this muscle in our laboratory. The choice of nasalis was based on the routine use of this muscle by another laboratory in Toronto, and also on the recent report of the technical superiority of RNS when recording over the nasalis muscle compared to the orbicularis in normal subjects 8…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The choice of frontalis was based on the historical routine use of this muscle in our laboratory. The choice of nasalis was based on the routine use of this muscle by another laboratory in Toronto, and also on the recent report of the technical superiority of RNS when recording over the nasalis muscle compared to the orbicularis in normal subjects 8…”
Section: Methodsmentioning
confidence: 99%
“…In addition, RNS sensitivities vary depending on the distribution of weakness (i.e., ocular vs. generalized MG) and severity of disease 3, 5, 7. One study in normal subjects demonstrated the technical superiority of repetitive stimulation of the facial nerve with recording over the nasalis muscle compared with recording over the orbicularis oculi muscle 8…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Then, six repetitive electrical stimuli were administered at a frequency of 3 Hz (Han et al, 1998;Ruys-Van Oeyen and Van Dijk, 2002) to obtain six identical waveforms (Fig. The study was reviewed and approved by the institutional review board.…”
Section: Methodsmentioning
confidence: 99%
“…Volunteers were recruited by posting fliers in the EMG laboratory and in the departmental bulletin boards. The amplitudes of individual waveforms and those of the waveforms between the two sites of stimulation were compared (Han et al, 1998;Ruys-Van Oeyen and Van Dijk, 2002). Waveforms were recorded from the frontalis muscle using surface electrodes.…”
Section: Methodsmentioning
confidence: 99%